The efficacy of a complex of vitamins B 1, B6 and B 12 in combination with nonsteroidal antiinflammatory drugs for pain control in osteoarthritis: meta-analysis of randomized controlled trials - E. S. Filatova; A. E. Karateev; S. I. Glukhova; A. M. Lila (Современная ревматология, 2025)
Pain control is the most important task in the complex treatment of osteoarthritis (OA). One of the promising methods to increase the efficacy of analgesics in OA may be the combined use of nonsteroidal antiinflammatory drugs (NSAIDs) with a complex of vitamins B1, B6 and B12 (СVB).Objective: to evaluate the efficacy of combination of NSAIDs + CVB compared to monotherapy with NSAIDs in the treatment of knee OA using a meta-analysis of randomized controlled trials (RCTs).Material and methods. We selected articles during the period 1981–2024 years using electronic databases PubMed (English-language sources), eLIBRARY.ru (Russian-language sources) and Yandex search engine. The search yielded a total of 55 publications on this topic. RCTs investigating the efficacy of CVB in patients with OA were presented in 5 articles, of which only 3 had a unified design that included a comparison of the therapeutic effect of the combination of NSAIDs + CVB and NSAIDs monotherapy. These papers were included in the meta-analysis, in which the dynamics of pain intensity on the visual analogue scale (VAS) and the WOMAC index were evaluated. A weighted mean difference (WMD) and the heterogeneity of the data (index I2) were calculated.Results and discussion. The meta-analysis included 3 RCTs (n = 298) with a duration of 3 to 8 weeks. The groups analyzed were homogeneous regarding the initial values of pain and the WOMAC index: the I2 index was 0%. The analysis of these parameters after treatment showed a slight heterogeneity: the I2 index for pain – 20%, for the WOMAC index – 39%. Initially there were no statistically significant difference between the main group (NSAID + CVB) and the control group (NSAIDs) in terms of pain level (by VAS): WMD=0.20 (95% CI, -0.05; 0.45). After treatment, the difference between the main and control groups in the dynamics of pain (by VAS) was statistically significant: WMD=-0.81 (95% CI -1.11; -0.50). Significant differences between the main and control groups in the baseline indicators and the dynamics of the WOMAC index were not found. No serious adverse reactions were detected in 3 RCTs.Conclusion. According to the meta-analysis of 3 RCTs, the combination of NSAIDs + CVB in OA reduces the severity of pain more effectively than NSAIDs monotherapy.